Few-Layered MoS2 Nanoparticles Covering Anatase TiO2 Nanosheets: Comparison between Ex Situ and In Situ Synthesis Approaches - Rosangela Santalucia; Tiziano Vacca; Federico Cesano; Gianmario Martra; Francesco Pellegrino; Domenica Scarano (Applied Sciences, 2020)
MoS2/TiO2 nanostructures made of MoS2 nanoparticles covering TiO2 nanosheets have been synthesized, either via ex situ or in situ approaches. The morphology and structure of the MoS2/TiO2 hybrid nanostructures have been investigated and imaged by means of X-ray diffraction (XRD) analysis and high-resolution transmission electron microscopy (HRTEM), while the vibrational and optical properties have been investigated by Raman, Fourier-transform infrared (FTIR), and UV−visible (UV–vis) spectroscopies. Different stacking levels and MoS2 nanosheets distribution on TiO2 nanosheets have been carefully evaluated from HRTEM images. Surface sites on the main exposed faces of both materials have been established by means of in situ FTIR spectra of CO probe molecule adsorption. The results of the ex situ and in situ approaches are compared to underline the role of the synthesis processes affecting the morphology and structure of MoS2 nanosheets, such as curvature, surface defects, and stacking order. It will be shown that as a result of the in situ approach, the reactivity of the TiO2 nanosheets and hence, in turn, the MoS2–TiO2 nanosheets interaction are modified.